ENGAGING ENGLISH VOCABULARY THROUGH DIGITAL STORYTELLING ACROSS EFL YOUNG LEARNERS - Beny Hamdani; Muhammad Darrin Zuhri; Hosnol Hotimah; Tjitra Ramadani (The Ellite of Unira, 2022)
This recent study aims to examine the improvement of students’ vocabulary mastery through digital storytelling at the fifth grade of elementary school Zainul Hasan Genggong Kraksaan Probolinggo and describe the implementation of digital storytelling in teaching vocabulary at the fifth grade of elementary school Zainul Hasan Genggong Kraksaan.  The research design is Classroom Action Research. The participants were the teacher (collaborator) and the fifth grade of elementary school Zainul Hasan Genggong Kraksaan Probolinggo. Data collection was an interview and vocabulary test. The data obtained were analyzed using descriptive qualitative and descriptive statistic. The findings revealed that the use of digital storytelling media was effective to engage students’ vocabulary mastery. It gives students to have chances to practice the vocabulary in their language skills. Meanwhile, the result of quantitative data showed that there was a significant and consistent improvement of students’ mean score in pre-cycle (44, 42), cycle 1 (45.03) and cycle 2 ( 73.89). Thus, there was approximately 29.42 point of improvement during the cycles. The result indicates that the use of digital storytelling media is effective to engage the students’ vocabulary mastery of the  fifth grade of elementary school Zainul Hasan Genggong Kraksaan Probolinggo.